2014
DOI: 10.1186/cc13900
|View full text |Cite
|
Sign up to set email alerts
|

Is high-frequency oscillatory ventilation more effective and safer than conventional protective ventilation in adult acute respiratory distress syndrome patients? A meta-analysis of randomized controlled trials

Abstract: IntroductionComprehensively evaluating the efficacy and safety of high-frequency oscillatory ventilation (HFOV) is important to allow clinicians who are using or considering this intervention to make appropriate decisions.MethodsTo find randomized controlled trials (RCTs) comparing HFOV with conventional mechanical ventilation (CMV) as an initial treatment for adult ARDS patients, we searched electronic databases (including PubMed, MedLine, Springer Link, Elsevier Science Direct, ISI web of knowledge, and EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
0
22
0
4
Order By: Relevance
“…An updated meta-analysis of 6 RCTs (1,608 subjects), including OSCAR and OSCILLATE, confirmed that HFOV does not significantly reduce mortality, despite leading to an improvement in oxygenation. 64 As such, HFOV cannot currently be recommended for routine use in adult patients with early moderate-to-severe ARDS.…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…An updated meta-analysis of 6 RCTs (1,608 subjects), including OSCAR and OSCILLATE, confirmed that HFOV does not significantly reduce mortality, despite leading to an improvement in oxygenation. 64 As such, HFOV cannot currently be recommended for routine use in adult patients with early moderate-to-severe ARDS.…”
Section: Current Evidencementioning
confidence: 99%
“…Physiological predictors of survival should be considered 66 : early changes in arterial oxygenation may identify patients with a greater proportion of recruitable lung, who are more likely to benefit from HFOV, whereas patients who require significant increases in vasopressors or with no improvement in oxygenation should be switched back to conventional mechanical ventilation. Although selected patients with severe ARDS may benefit from HFOV, Gu et al 64 pointed out in a recent meta-analysis that these patients are rare and difficult to identify. Future studies will have to consider a new approach to the use of this ventilatory strategy in subjects with ARDS.…”
Section: State Of the Art And Future Prospectsmentioning
confidence: 99%
“…Recent studies have shown that ventilation regimes working on principle of intermittent positive pressure ventilation (IPPV), which use small tidal volumes (4-6 ml/ kg body weight) and appropriate values of positive end-expiratory pressure (PEEP, 0.4-0.7 kPa), may protect the lung of patients of all age groups, including neonates, from an additional injury (Dargaville 2012;Brown and DiBlasi 2011). However, other studies have not confirmed any clear differences between CMV and HFO (Maitra et al 2015;Gu et al 2014). HFO supplies effective gas exchange at frequencies of 5-15 Hz, or higher, with tidal volumes smaller than the dead space volume and high values of PEEP keeping the chest in prone position (Chowdhury and Greenough 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent meta-analysis of 1,608 patients, including the OSCILLATE and OSCAR cohorts, confirmed no increase in barotrauma or hypotension with HFOV, but found no significant reduction in 28-or 30-day mortality. 28 In addition, a follow-up study evaluating 1 year quality-adjusted years of life after participation in the OSCAR trial suggested no economic advantage to HFOV in terms of incremental costs and recommended that further research on improving severe ARDS ventilation should concentrate outside of HFOV. 29 At this point, HFOV use for severe ARDS in adults cannot be recommended routinely outside of salvage situations.…”
Section: Ventilationmentioning
confidence: 99%